(untitled) (Medico Legal Update, 2021)
Nosocomial infections are diseases acquired within 48 hours or more of hospital admission or within 30 days of discharge. The objectives of the study were to assess the knowledge, attitude and practice regarding nosocomial infection and their prevention among health care workers. To determine the relationship between knowledge, attitude and practice regarding nosocomial infection and their prevention among health care workers. To find out association between the knowledge, attitude and practice regarding nosocomial infection and their prevention among health care workers. The research design selected for the study was descriptive research design and a total 100 health care staff were selected as study sample tool was used for data collection. Self-introduction was given and purpose of gathering the information and nature of study was explained before taking information through non probability convenient sampling technique. A self- structured questionnaire, consent was signed by participants. The result revealed that the most of the health care staff 76(76%) had excellent knowledge regarding nosocomial infection and their prevention less than half, 43(43%) had positive attitude regarding nosocomial infection and their prevention. On the contrary, 74(74%) had excellent practice regarding nosocomial infection and their prevention. On applying the spearman correlation test, relationship between knowledge and attitude was found to be significant at p<0.05. Hence, researchers concluded that the present study was undertaken to identify the level of knowledge, attitude and practice regarding nosocomial infection and prevention among health care staff in selected hospitals of Punjab. The finding showed that majority of the participants had excellent knowledge and practice. There were gaps in relationship between knowledge and practice and attitude which is found to be not significant at p<0.05.